Distanciamento social e privação ocupacional durante a pandemia da Covid 19: implicações na saúde mental de pessoas idosas - Pedroso, Jéssica da Rocha (2022)
Introduction: The viral disease COVID-19 has become a worldwide concern due to its rapid proliferation and severe manifestation in some cases. Thus, concerns arose about the proliferation of the virus and aggravations of the disease, especially in the elderly population. With the aim of mitigating the spread of the virus, measures were implemented to restrict the movement of people and physical contact, such as isolation of the infected, quarantine for those exposed and social distancing for the population. These restrictions have brought several damages to people's health, causing possible impacts on mental health, which may lead to occupational deprivation and changes in the performance of occupations, on the other hand, new occupational engagements may be discovered. Objective: To describe the impacts of social distancing on mental health and to verify situations of occupational deprivation and occupational engagement in the elderly during the pandemic. Methodology: Cross-sectional study, with elderly people aged 60 years and over, both sexes and genders, residents of Santa Maria and participants in social groups linked to the Integrated Center for Studies and Support for the Elderly - NIEATI/UFSM. Data collection was carried out through an interview by telephone with the application of an elaborate questionnaire and the Patient Health Questionnaire - 4 (PHQ-4) instrument, to screen for depressive and anxiety symptoms. Results: The sample had 55 participants, there was a predominance of female individuals, white, aged between 70 and 79 years, with 9 years of schooling or more, married, with a monthly family income greater than one minimum wage, residing only with the spouse and of the Catholic religion. 97.27% of the sample reported suffering occupational deprivation during social distancing, 32.7% reported that they suffered impacts on occupational performance and 32.7% were able to engage in new occupations. As for screening for symptoms of depression and anxiety, using the PHQ-4 instrument, 10.9% of the sample showed indicators of depressive symptoms and 16.4% for anxiety symptoms. The depression variable was associated with the variables social distancing (p=0.0031) and occupational performance (p=0.012). Anxiety, on the other hand, showed a significant association for the occupational performance variable (p=0.046). Conclusion: In this study, the occurrence of situations of occupational deprivation that bring several damages to people's health was observed. It was also observed that a small portion of the participants managed to engage in new occupations during the period. Discovering new occupational engagements can bring health benefits and minimize psychological illness.